Evangelical Educational Association and Its Influence on Social Formation (CIPEEX, 2025)
This study analyzes the origin and influence of the Evangelical Educational Association (AEE) on education and the social development of Goiás since 1947. The research aims to understand how the AEE, grounded in Christian principles, has contributed to the educational and moral formation of society in Goiás. Drawing on Émile Durkheim’s theory of moral education and Vishal Mangalwadi’s perspective on the integration of biblical values in learning, the study highlights the relationship between education, morality, and social cohesion. Methodologically, it combines historical research, theoretical analysis, and direct observation at UniEVANGÉLICA. The results demonstrate that the AEE has consistently promoted academic excellence while emphasizing moral, ethical, and spiritual development. Programs such as the Volunteer Initiative “Hands for Good” and the extension project “Law in Action: Legal Guidance for Citizenship” exemplify the institution’s integration of social responsibility with education. The conclusion reinforces that the AEE plays a crucial role in forming ethical and responsible citizens, strengthening Christian values, and contributing to a fairer and more supportive society.
Keywords: Christian Education; Social Development; Morality.